An assessment of various strategies to curb Gender Imbalance in Tertiary Institutions in North-Central Nigeria (International Journal of Educational Technology Research, 2024)
This study assessed the various strategies to curb gender imbalance in tertiary institutions in North-central Nigeria. The research design of this study was a descriptive survey. The population of the study comprises all the academic staff in the North-central zone. The sample size for the study was four hundred and eighty (480) selected from two federal and two state universities in the region using a simple random sampling technique. The instrument for data collection was the structured questionnaire developed by the researcher titled “Strategies to Curb Gender Imbalance in Tertiary Institutions in North-central Nigeria Questionnaire). The instrument was face-validated by two experts from Educational Administration and Planning, in the Department of the Educational Management University of Abuja, all from the faculty of Education. Descriptive statistics was used for data analysis. Mean scores from 2.50 was considered accepted while any mean scores below 2.50 was considered rejected. The study concluded that that full implementation of gender policies in areas of appointment, recruitment and students admission in all tertiary institutions in North Central, Nigeria, Capacity building for tertiary institutions managers on gender issues, Tertiary institution sensitization programme on gender equality, Rewarding institutions with gender friendly policies and programme, ensure implementation and report gender policies implementation level annually and involvement of International organizations, private institutions and Non-governmental organization on gender issue to participate and establish clubs in various tertiary institutions are the various strategies to curb gender inequality in all tertiary institutions in North Central, Nigeria